Efficacy and Safety of Tenofovir in Preventing Perinatal Hepatitis B in Jakarta - Muzakar, Cholid; Sandhiutami, Ni Made Dwi; Ramadaniati, Hesty Utami; Sriyono, Bimantoko Hadi (Sciences of Pharmacy, 2026)
Vertical transmission of hepatitis B virus (HBV) remains a major public health challenge in Indonesia, particularly among pregnant women with high viral loads. Tenofovir disoproxil fumarate (TDF) has been recommended to prevent perinatal transmission; however, local data regarding its efficacy and safety remain limited. This study aimed to evaluate Analyzing the effectiveness and safety of TDF in HBsAg-reactive pregnant women and its relationship with the infant's HBsAg status is necessary. An observational cohort study was conducted on 103 HBsAg-reactive pregnant women at five referral health facilities in Jakarta. Maternal effectiveness was measured by changes in SGPT and SGOT levels before and after therapy using the Wilcoxon test. Safety was assessed based on adverse events, pregnancy complications, and renal function using the chi-square test. Infant effectiveness was analyzed based on HBsAg status and tested using multivariate logistic regression. TDF significantly reduced SGPT and SGOT levels (p < 0.001). No significant association was found between TDF duration and adverse events, complications, or renal impairment (p > 0.05). Ninety-one-three percent of infants were HBsAg non-reactive, and 93.2% received complete hepatitis B vaccination. Complete vaccination (OR = 414.52; p < 0.001) and the absence of pregnancy complications (OR = 0.048; p = 0.021) were the main protective factors. TDF is safe and effective in preventing vertical transmission of HBV. Successful prophylaxis is highly dependent on infant vaccination and maternal health. These results support the integration of TDF into the national hepatitis B elimination program.